Major advances in bioengineered heart implants. (Research'eu results magazine)
'Tissue engineering' (TE) and 'regenerative medicine' (RM) will be at the core of heart surgery in the future. An EU initiative generated a platform of expertise to supply top-class training for researchers to enable development of bioengineered cardiovascular implants.